ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII SMP NEGERI 31 PADANG TAHUN PELAJARAN 2019/2020 - Vivi Silvia Riza (Departemen Matematika, 2020)
Mathematical communication skills are very important in leaming mathematics in schools, because mathematical communication skills are one of the abilities that every student must have and are also a tool that can be used to solve problems, especially math problems. The purpose of this study was to describe the mathematical communication skills of high-ability students, medium-capable students, and low-ability students in solving math problems in class VII SMP Negeri 31 Padang for the 2019/2020 academic year. The subjects of this study were 31 students of class VII-5 SMP Negeri 31 Padang. The data used is the result of an assessment of the student's answer sheet on the daily assessment of the linear equation and inequality material for one variable using a rubric for indicators of mathematical communication skills. Students' mathematical communication skills are measured based on indicators of mathematical communication skills, namely (1) expressing mathematical ideas in writing; (2) explain mathematical ideas, strategies, situations and relations in writing using algebra; (3) use complete sentences, symbols, tables, diagrams or other media to clarify the situation or problem. The results show (1) The most prominent indicator for highly skilled students is the first indicator, while the least prominent indicator for highly skilled students is the third indicator; (2) The most prominent indicator for moderately capable students is the first indicator, while the least prominent indicator for highly skilled students is the third indicator; (3) The most prominent indicator for low-skilled students is the first indicator, while the least prominent indicator for highly skilled students is the second indicatoKeywords - Mathematical communication skills, Mathematics